Simulation of traffic signal using fuzzy logic - Wong, Wei Wei (2019)
The aim of this thesis is to simulate the fuzzy intelligent traffic for the optimal controlling of the traffic green signal flow at the traffic intersections. The proposed fuzzy control system is used to effectively manage the urban traffic junction of the intersections in Malaysia. The importance of the proposed fuzzy intelligent traffic control system consists in consideration of uncertainty and vagueness of information about the values of the input and output parameters of the system. Using the input parameters and based on the inferences from the fuzzy rules, the fuzzy traffic controller decides the priority street to become the green light on the next phase in the traffic intersection. Computer simulation is carried out using Matlab software. The result of select the green light on the intersection road is purposed using the Mamdani inference engine. The effectiveness of the fuzzy traffic controller with four input parameters is explained.